Study on the influence of polyurethane foam aluminum on the damping effect of tunnel - Cheng Wang; Feng Gao; Xukai Tan; Dongmei You (Systems Science & Control Engineering)
A shaking table model test of the tunnel was carried out to compare the damping effects of polyurethane foam aluminum(AF/PU) and sponge rubber. The test shows that the damping effect of polyurethane foam aluminum is better, and the dynamic earth pressure and strain values of each measuring point of the tunnel lining are relatively smaller. The ANSYS software was used for the ground motion simulation. The first principal stress and first principal strain of the lining were compared and analysed between the two types of damping layers. It was found that the damping effect of AF/PU was better, which is consistent with the test results. The damping effects of AF/PU with thicknesses of 10, 20, and 30 cm were 22.3%, 29.03%, and 31.41%, respectively. The damping effect increases with an increase in thickness, but the growth rate slows.